2004
DOI: 10.1074/jbc.m402373200
|View full text |Cite
|
Sign up to set email alerts
|

Cystic Fibrosis Transmembrane Conductance Regulator Differentially Regulates Human and Mouse Epithelial Sodium Channels in Xenopus Oocytes

Abstract: The cystic fibrosis transmembrane conductance regulator (CFTR), in addition to its well defined Cl ؊ channel properties, regulates other ion channels. CFTR inhibits murine or rat epithelial Na ؉ channel (mENaC or rENaC) currents in many epithelial and non-epithelial cells, whereas murine or rat ENaC increases CFTR functional expression. These regulatory interactions are reproduced in Xenopus oocytes where both the open probability and surface expression of wild type CFTR Cl ؊ channels are increased when CFTR i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
39
3

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 32 publications
10
39
3
Order By: Relevance
“…Amiloride inhibits these apically located Na ϩ channels with varying efficacies. CFTR down-regulates amiloridesensitive ␣␤␥ ENaC activity in Xenopus oocytes (3)(4)(5)(6)(7)(8)(9)(10)(11). These results are in agreement with observations from normal and CF tissues (12)(13)(14)(15)(16)(17).…”
supporting
confidence: 82%
See 2 more Smart Citations
“…Amiloride inhibits these apically located Na ϩ channels with varying efficacies. CFTR down-regulates amiloridesensitive ␣␤␥ ENaC activity in Xenopus oocytes (3)(4)(5)(6)(7)(8)(9)(10)(11). These results are in agreement with observations from normal and CF tissues (12)(13)(14)(15)(16)(17).…”
supporting
confidence: 82%
“…Also, amiloride sensitivity, ion selectivity, and single channel conductance are different from native epithelial Na ϩ channels (23). In addition, the putative CFTR channels in Calu-3 cells (but not heterologously expressed CFTR in oocytes) exhibit a basal, glibenclamide-inhibitable Cl Ϫ current before the addition of cAMP (4,7,8,38). The mechanisms for the differences between cloned and native epithelial cation and anion channels are not clear.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequent Thr663Ala variant is situated in the COOH terminus of the protein, which shows considerable interspecies variability (15 ). These interspecies differences in the 20 C-terminal amino acid residues also seem to explain species differences for regulatory proteins such as cystic fibrosis transmembrane conductance regulator.…”
Section: Discussionmentioning
confidence: 99%
“…36 It has also been reported that the interaction of mouse and human CFTR with ENaC is species specific. 37 Thus it is possible that the human CFTR, due to sequence differences, does not function properly in mouse cells under all conditions. This could be the result of altered glycosylation, mis-localization as a result of altered binding to other proteins, or a failure to be activated by the murine signaling (kinase) pathways.…”
Section: Cftr Expression In Murine Ciliated Cells Le Ostrowski Et Almentioning
confidence: 99%